Castigo físico como sanción aplicada a la justicia indígena frente al derecho constitucional a la integridad física. - Cabascango, Nancy F. (2021)
Ecuador is a Constitutional State of rights that recognizes indigenous peoples and communities their own jurisdiction; establishing a new system of administration of justice. The objective of this work was to reveal the contradiction that exists between the application of traditional practices, without due proportionality, regarding sanctioning indigenous justice, with the protection of the constitutional right to physical integrity. The qualitative approach and the descriptive documentary type of research using the analytical method were used. A total of 20 acts of resolutions applied by the administration of indigenous justice in the Cayambe and Pedro Moncayo cantons of the Pichincha Province (2018-2019) were analyzed. It was concluded that, from the characterization of the crimes and the application within their territories, of the 20 cases studied, physical punishment stands out above the others. It was possible to determine that there is obviously a contradiction between indigenous justice and the constitutional rights that protect the physical integrity of people, due to the fact that when applying these punishments as sanctioning, their decisions are not subject to due proportionality. It is recommended to limit these sanctions in the practice of indigenous justice, since it was evidenced that doing so violates the innate rights of the human being.